2013
DOI: 10.1002/jat.2877
|View full text |Cite
|
Sign up to set email alerts
|

Role of surface charge and oxidative stress in cytotoxicity and genotoxicity of graphene oxide towards human lung fibroblast cells

Abstract: Recently, attempts have been made to apply graphene oxide (GO) in the field of biology and medicine, such as DNA sensing and drug delivery with some necessary modifications. Therefore, the toxicity of GO must be evaluated before it is applied further in biomedicine. In this paper, the cytotoxicity and genotoxicity of GO to human lung fibroblast (HLF) cells have been assessed with methyl thiazolyl tetrazolium (MTT), sub-G1 measurement and comet assays, and the mechanism of its toxicity has been explored. Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
139
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 45 publications
9
139
2
1
Order By: Relevance
“…60 Previous studies have indicated that the interaction of nanoparticles with the cell membrane triggered ROS generation and oxidative stress, which may cause breakdown of membrane lipids, alterations in metabolic pathways, and apoptosis. 88,90,91 The increase in ROS production by GO and RES-rGO is in agreement with the results of the WST-8 and LDH assays, suggesting that GO and RES-rGO induce cytotoxicity via oxidative stress. Reddy et al 92 have shown that multi-walled carbon nanotubes induce oxidative stress-dependent cytotoxicity in cultured human embryonic kidney cells.…”
Section: Concentrations (µG/ml) Ros Generation (Fold Increase)supporting
confidence: 86%
See 1 more Smart Citation
“…60 Previous studies have indicated that the interaction of nanoparticles with the cell membrane triggered ROS generation and oxidative stress, which may cause breakdown of membrane lipids, alterations in metabolic pathways, and apoptosis. 88,90,91 The increase in ROS production by GO and RES-rGO is in agreement with the results of the WST-8 and LDH assays, suggesting that GO and RES-rGO induce cytotoxicity via oxidative stress. Reddy et al 92 have shown that multi-walled carbon nanotubes induce oxidative stress-dependent cytotoxicity in cultured human embryonic kidney cells.…”
Section: Concentrations (µG/ml) Ros Generation (Fold Increase)supporting
confidence: 86%
“…The treatment with RES-rGO and H-rGO caused a more pronounced negative effect on the membrane integrity of A2780 cells than GO, indicating enhanced cytotoxicity, whereas RES-rGO and H-rGO show significant leakage. Zhang et al 83 have reported that graphene aggregation induced LDH leakage in rat pheochromocytoma PC12 cells, while Wang et al 88 have demonstrated that GO caused cytotoxicity and genotoxicity in human lung fibroblast cells, which correlated with its effects on cell membrane integrity and depended on particle size, shape, composition, and surface charge and chemistry.…”
Section: Effect Of Res-rgo On Membrane Integritymentioning
confidence: 99%
“…GO ( Figure 9C) showed obvious toxicity towards MRC-5 as compared to the untreated cells, even from concentrations as low as 5 μg/mL. A previous investigation by Wang et al 82 supports this observation, where GO was found to induce cytotoxicity, genotoxicity, and oxidative stress to MRC-5 cells. In contrast, RGO showed no cytotoxicity towards normal cell lines with the cell viability above 90%, even at 50 μg/mL.…”
supporting
confidence: 74%
“…They also hypothesized that positively charged particles might disrupt the charge balance of the cell membrane and induce cell damage at a later stage, while negatively charged NPs have an inferior rate of endocytosis and do not utilize the clathrin-mediated endocytosis pathway. 50 The results from our study did not identify such correlations among the CNPs investigated, either with regard to positive/negative charge or ζ-potential. This indicates that the key toxicological factor may depend on another parameter, such as the identity of functional groups on the CNP structures.…”
contrasting
confidence: 78%
“…According to Wang et al, 50 the higher ζ-potential of GO and GO derivatives causes more severe cell damage, but when the level of charge on its surface was high enough, charge did not directly correlate with toxicity. They also hypothesized that positively charged particles might disrupt the charge balance of the cell membrane and induce cell damage at a later stage, while negatively charged NPs have an inferior rate of endocytosis and do not utilize the clathrin-mediated endocytosis pathway.…”
mentioning
confidence: 99%